Influence of Market Mix Strategy (Marketing Mix) Towards the Increase in the Number of New Students of SDIT Ar-Treatise Seteluk - Saprianto Saprianto; Ahmad Yamin; Dedi Supriadi (International Journal Labs, 2022)
Background: Education is one of the efforts made to improve the quality of human resources which in essence helps, humans, to be smart, smart and smart. The school is one provides institutions that provide education and learning for children who are not only normal but also have special needs. Objective: To explain the effect of the educational marketing mix at SDIT Ar-Risalah on the increase in the number of students. Method: Based on the title proposed by the researcher, namely